PENDIDIKAN DAN KEUTAMAAN ORANG BERILMU - Abdul Wahab Syakrani; Rahmaniah ulfah; Siti Amaliyah Nur Azhari; Siti Annisa; Umi Habibah (CV. ADIBA AISHA AMIRA, 2022)
A commendable human is a human who is knowledgeable and puts into practice his knowledge, the position of this type of human is the same as fertile soil that can absorb water, then the water is beneficial for the soil itself and is able to grow plants so that it is beneficial for others. Some of the virtues of knowledge mentioned in the above hadith; 1) Allah wants good for him, 2) Get a reward that never breaks and As a milestone of knowledge.